Analysis of Community Preparedness in Facing Fire Disasters in Desenly Populated Settlements in Samarinda City - Frisca Marindayanti; Yaskinul Anwar; Yulian Widya Saputra (Future Space: Studies in Geo-Education, 2024)
Densely populated settlements in Samarinda City are fire-prone areas. This research aims to determine the level of community preparedness in facing fire disasters, as well as the factors that influence community preparedness. Observation, questionnaires, interviews, and documentation were carried out data collection in this research. The sampling technique used was cluster sampling with a sample size of 114 people. Preparedness data analysis using scoring and categories. The research results show that the majority of the community's preparedness level is in the ready category (61%), where economic, social, and physical factors influence community preparedness. Economic factors can be seen from the absence of insurance or disaster emergency funds, while the social factor is community interaction and participation in fire disaster outreach and training activities. Physical factors that have an influence are the community's efforts to overcome fire-prone settlements by installing water taps outside the house, contacting PLN if there are electricity network problems and building wells. Collaboration between communities and support from the government through the Pro-Bebaya Program is important to increase community preparedness in facing fire disasters.